OP29 Tofacitinib in ulcerative colitis: Real-world evidence from Eneida Registry. (15th January 2020) - Chaparro, M; Garre, A; Mesonero, F; Rodríguez, C; Barreiro-de Acosta, M; Martínez-Cadilla, J; Arroyo, M T; Manceñido, N; Sierra-Ausín, M; Vera-Mendoza, I; Casanova, M J; Nos, P; et al.
Abstract: Background: Our aim was to evaluate the effectiveness and safety of tofacitinib in ulcerative colitis (UC) in real life. Methods: Patients from the prospectively maintained ENEIDA registry treated with tofacitinib due to active UC were included. Clinical activity and effectiveness were defined based on Partial Mayo Score (PMS). The short-term response was assessed at week 4, 8 and 16. The last-observation-carried-forward method was used in patients that stopped tofacitinib before the time-points for clinical assessment. Variables associated with short-term remission at week 8 were identified by logistic regression analysis. The cumulative retention rate and the cumulative incidence of relapse over time were assessed by survival curves. Cox-regression analysis was performed to identify predictive factors of tofacitinib discontinuation or relapse over time. Data quality was assessed by remote monitoring. Results: 113 patients were included (Table 1 and Figure 1) and exposed to tofacitinib a median of 44 (interquartile range = 30–66) weeks. Response and remission at week 8 were 60% and 31%, respectively (Figure 2). In multivariate analysis, higher PMS at week 4 [odds ratio (OR)=0.2; 95% confidence interval (CI) = 0.1–0.4] was the only variable associated with the likeliness of achieving remission at week 8. Higher PMS at week 4 (OR = 0.5; 95% CI = 0.3–0.7) and higher PMS at week 8 (OR = 0.2; 95% CI = 0.1–0.5) were associated with lower probability of achieving remission at week 16. Twenty per cent of those without remission at week 4, and 12% of those without remission at week 8, achieved remission at week 16. A total of 45 patients (40%) discontinued tofacitinib over time (Figure 3); the discontinuation rate was 34% and 46% at 24 and 52 weeks, respectively. PMS at week 8 was the only factor associated with tofacitinib discontinuation [Hazard ratio (HR) = 1.5; 95% CI = 1.3–1.6)]. A total of 33 patients had remission at week 8; from them, 65% relapsed 52 weeks after achieving remission; 9 patients increased the dose to 10 mg /12 h and 5 reached remission again. No factors associated with relapse over time were identified. Eighteen patients had adverse events (4 hypercholesterolaemia, 2 herpes zoster, 3 infections, 2 dyspnoea, 1 neoplasia, 1 lymphopenia, 1 headache, 1 hypertriglyceridaemia and 4 others). No thromboembolic events were reported. Conclusion: Tofacitinib is relatively effective in UC patients in real practice even in a highly refractory cohort. Only 10% of the patients without remission at week 8 reached remission at week 16. A relevant proportion of patients discontinue the drug over time, mainly due to primary failure. Over 60% of patients that achieve remission, relapse over time. Safety was consistent with the known profile of tofacitinib